Design and Construction of a Plasma Sterilizing Machine Using Locally Available Materials. - Kule, Joseph Muhana (Kabale University, 2024)
The spread of pathogenic microbes from one individual to another has become a serious problem for many health workers and civilians even when some sources are taken for granted in many developing countries like Uganda. The main focus of the study was to construct and design a plasma sterilizing machine and elucidate its efficiency by carrying out a microbial sterilization case study on the saloon shaving machines used in the southern region of Kabale Municipality. Some saloons were sampled purposively and the blades of the shaving machines were inoculated to make a sample solution of about 80cm3 from which I cm3 sample was placed on microscopic slides and observed under medium and high power to find out the microbial population in the samples made. All the sample solutions were found to contain a bigger number of microbes. Locally available materials were used to make a sterilizing machine which was found to be 99A% deficient at eradicating the observed microbes. ll can therefore, be suggested that via the use of unsterilized shaving machines in Kabale municipality, people around might have been contacting the pathogenic microbes and this could be one of the causes and sources of diseases transferable from one individual to another however applying a few concepts of physics suitable remedies can be put on ground to minimize the risks in an environmentally friendly way.